Drogas anticâncer em efluente hospitalar: método, ocorrência, avaliação preliminar de risco, degradação por fotólise e ozonização - Souza, Darliana Mello (2018)
In the last decade, the demand for anti-cancer drugs has grown considerably. These products are one of the drug classes with great potential to cause harm to the environment, even in low concentrations, and may have cytotoxic, genotoxic, mutagenic, carcinogenic and teratogenic effects. Factors such as misallocation, inefficiency of sewage treatment systems and increasing drug consumption have contributed to environmental contamination with these emerging contaminants. These aspects motivated this research, dedicated to the study of the occurrence and chemical degradation of four anticancer drugs, such as doxorubicin, daunorubicin, epirubicin and irinotecan. The first stage of the study consisted of the development of a chromatographic method using solid-phase extraction and dispersive liquid-liquid microextraction to quantify these four anti-cancer drugs. The method developed was used in the quantification of these antineoplastics in the hospital effluent of the Federal University of Santa Maria. The determined concentrations were then preliminarily evaluated for ecotoxicological risk. Photolysis and ozonation processes were chosen as 'advanced processes' to examine the degradation of anti-cancer drugs, as posttreatment to the microbiological system of septic tanks. The results of the validation of the method developed show coefficients of determination superior to 0,99 and values of recovery between 74% and 105%, with intraday precision <15%. The quantification limit was 1.0 μg L-1 and the matrix effects were negligible. Thus, the parameters necessary to evaluate the analytical reliability of the results and to guarantee the quality of the experiments were obtained successfully, according to the guide of analytical quality control and method validation procedure SANTE and in accordance with the guidelines established by ABNT NBR ISO / IEC 17025. This makes it possible to use the proposed method for the determination of the anti-cancer drugs in concern, in hospital effluent samples. In the study of the effluent generated by the University Hospital, in the period of seven days, the four antineoplastics were quantified in the range of LOQ≤1.0 μg L-1 to 6.22 μg L-1. A preliminary assessment of the concentrations of anti-cancer occurrences revealed that they constitute a high ecotoxicological risk. The in-bench scale experiments using advanced degradation processes of the four antineoplastics, both via photolysis and via ozonation, complement the microbiological processes of effluent treatment. Finally, ozonation showed, as expected, more efficient degradation of anti-cancer molecules compared to photolysis.